Prevalence of methicillin resistant Staphylococcus aureus in selected seafood markets and aquaculture farms in Kerala, south-west coast of India - Murugadas, V.; Joseph, Toms C.; Reshmi, K.; Lalitha, K. V. (Indian Journal of Fisheries, 2016)
A study was carried out to understand the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) in selected seafood commodities, market environment as well as in aquaculture farms in Kerala, along the south-west coast of India. Two hundred and thirty three samples comprising finfish, crustaceans, molluscs and fishery environmental samples from markets as well as aquaculture farms were collected and screened for the presence of MRSA. The S. aureus isolates obtained from the samples were checked for resistance to methicillin, oxacillin and cefoxitin by antimicrobial sensitivity test and further confirmed by oxacillin agar screening method. A multiplex PCR was employed targeting mecA, nuc and 16s rDNA genes to differentiate S. aureus and MRSA from other staphylococci. It was found that 13.4% of the samples harboured MRSA while the overall prevalence of S. aureus was found to be 36.5%. This study has clearly indicated high prevalence of methicillin resistant S. aureus strains in the seafood as well as in environmental samples from seafood markets and aquaculture farms in Kerala. The prevalence of methicillin resistant strains of staphylococci in fish indicates high risk associated with fish handlers and fish farmers.